A Longitudinal Study On Prevalence Of Doping And The Perception Towards Anti-Doping Among Tamil Nadu Youth Football Players - Dr. Nikhil Roy M; Prof.Dr. Dobson Dominic; Dr. Praveen R; Dr.Koushik K V S (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Unintentional use of prohibited substances has led to anti-doping violations among Indian sports players. This study assessed the knowledge, attitude, and practices regarding anti-doping among youth football players. Methods: A longitudinal study used a pre-validated questionnaire to evaluate attitudes toward performance-enhancing substances and anti-doping rules, followed by a health education session to assess its impact through a post-test. Results: Only 58.27% were aware of WADA/NADA, and just 28.06% understood doping violations. Discussions with physicians were low at 15%. Post-education, 74% reported improved knowledge, and 62% noted a positive attitude change. Conclusion: Low awareness of prohibited substances is concerning. Recommendations include awareness campaigns, web-based materials, and integrating anti-doping education into curricula.